Food safety knowledge and practices of food handlers in selected carinderias in Miagao, Iloilo. - Martinez, Ferncy Dahl C.
Food service establishments prepare and serve food that can be consumed either on or off the premises. According to DOH (2000), carinderia is an example of a food service establishment. Carinderia is categorized as a BSBE (barangay micro business enterprise) which serves ready-to-eat food in markets and roadsides. The study aimed to assess the food safety knowledge and practices of food handlers in carinderias in Miagao Iloilo. Microbial characteristics of food contact surfaces (FCS) were assessed through Aerobic Plate Count (APC), total coliforms, detection of S. aureus and E. coli by swab contract method. A total of 7 carinderias participated in the study and 3 FCS were subjected to microbiological characterization. The profile of the handlers showed that majority of the food handlers? age ranging from 21-30 years old and most of them are women (78.6%). Out of 14 food handlers, 35.7% reached tertiary level while 64.3% attained high school level. Selected carinderias have clean selling areas, however, only 1 has a sanitary permit display and handwashing facility. Food handlers exhibited awareness in the importance of personal hygiene, cross contamination and handling. The common practice of food handlers includes handwashing, usage of clean chopping board and providing clean utensils while wearing the proper attire during food handling is least practised. APC of food contract surfaces from selected carinderias exceeded the 100 CFU/cm2 limit (Lambrechts et al., 2014). The presence of Staphylococcus aureus and Escherichia coli on FCS emphasizes the improvement of sanitation practices observance of proper cleaning and sanitation can help minimize risk of cross examination. Local government unit of Miagao should monitor the compliance of food establishments to regulatory requirements and conduct training programs for food handlers and food business operators.